Public Policy Challenges Facing Higher Education in the American West - Goodchild, Lester F.; Jonsen, Richard W.; Limerick, Patty; Longanecker, David A.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Public Policy Challenges Facing Higher Education in the American West is the first regional public policy study of American higher education.
Keywords: Science; Science; Science, general